A potentiometric technique for rapid carbon dioxide determination - Calbo, Adonai Gimenes; Martins, Eduardo Souza (Pesquisa Agropecuaria Brasileira, 2014)
Based on the proportionality between the pH of a diluted solution of sodium bicarbonate and with the logarithm of carbon dioxide partial pressure in the vapour phase, a new technique to measure carbon dioxide is proposed. The technique consists of taking air aliquots using 2 ml polycarbonate siliconized syringes with 1 mM of NaHCO3 + 0,099M of KCI solution with low dissolved carbon dioxide content. The solution and air aliquots rest for 24 hours, at 30°C, and then, pH measurements were taken without permiting the solution to get in touch with the environmental air. This technique led to the following equation: log (CO2) = 8.516 - 1.071 pH where CO2 is the concentration of carbon dioxide in the air in mg/l.